The effect of different levels of Azolla pinnata on the growth and laying performance of native ducks (Anas domestica) - Nisperos, Marietta Panelo (Animo Repository, 1988)
The effect of different feeding levels of Azolla on the growth and laying performance of native ducks (Anas domestica) was studied. The ANOVA tests showed no significant differences among treatments in terms of feed consumption, total gain in weight, rate of growth and feed per gain ratio. However, statistically significant differences were found among treatments in terms of egg production, egg weight, kilogram feed to produce a dozen eggs, and age at start of lay. Ducks fed with Azolla exhibited poor egg laying performance and produced lighter eggs, these characteristics were observed to decrease as the levels of Azolla were increased in the diet. None of the ducks fed with different feeding levels of Azolla showed any visible adverse effects.